The contribution of tourism to coastal livelihoods in Ponta do Ouro, Southern Mozambique - Come, Juliana ArsÃ©nio (Department of Environmental and Geographical Science, 2015)
Tourism is increasingly seen as a panacea for the problems of rural areas, especially in developing countries. It is promoted by governments and international development organizations as a vehicle for achieving development, poverty reduction and economic growth. However, tourism has resulted in many unwanted economic, social, cultural and environmental consequences for local communities. Through a case study conducted in Ponta do Ouro, Southern Mozambique, this research sought to investigate the contribution of tourism to coastal livelihoods. The research assessed the extent to which tourism contributes to livelihoods of coastal communities of Ponta do Ouro, and their perception of benefits and negative impacts associated with tourism. Qualitative methods were used to collect data and included five focus group meetings, 46 key informant interviews, and participant observation. Findings of this study reveal that despite providing employment and other economic benefits to the livelihoods of the community of Ponta do Ouro, tourism also resulted in negative impacts on community livelihoods. These included overcrowding during high tourism seasons, loss of access to public land, rising prices of properties, goods and services, and an increase in crime, alcohol use and pollution. Therefore a pro-poor tourism approach is recommended as an attempt to ensure that benefits of tourism are better distributed and serve the needs of the local and broader community in terms of infrastructure development and improvement of social services and facilities.